Leadership teams - Wageman, Ruth (Henry Stewart Talks, 2013)
Leadership teams underperform, Definition of leadership teams, Leadership team effectiveness, Studies of senior leadership teams and teams of environmental activists, Four ironies about leadership teams, Why leadership teams have unclear purposes, Why leadership teams have fuzzy boundaries, Four kinds of leadership teams, Misuse of team meeting time, Leadership team tasks and norms of conduct, Authority dynamics, How to design and lead leadership teams, Shared leadership, New research in leadership teams, Community collaboratives and multi-sector teams, Articulating shared purposes, 6 conditions for leadership team effectiveness, Senior leadership teams book
Reviewed at 2017/02/27